PENELITIAN TINGKAT KEPUASAN PELANGGAN SEBAGAI PREDIKTOR TERHADAP TINGKAT KESETIAAN PELANGGAN PROVIDER HANDPHONE - Muhammad Nur Nasution (Media Riset Bisnis & Manajemen, 2002)
Customer satisfaction has been an integral partof mission and goal ofimost organizations in order to be able to face tough competition. The customer feels satisfied if the product is much better than his expectation. Based on the data taken from "Multokotomis" questionnaire consisting of alternative answers which should be chosen by respondents and use given a value of 5,4,3,2 and 1. Those are six dimension of customer satisfaction measurements in the field of services, those are, the availability of supports, the responsiveness of supports, the timelines of supports, the completeness of supports, the pleasantness of supports and the overall satisfaction. In addition to that, there are five dimension of customer loyalty measurements such as, the repeat patronages, the self stated retention, the price insentivity, the resistance of counter persuasion and the likelihood of spreading positive word of mouth. The research revealed that the degree of customers' satisfaction can be used the predict to customers' loyalty.